Designing and evaluating complex interventions to improve health care. Issue 7591 (1st March 2007) - Campbell, Neil C; Murray, Elizabeth; Darbyshire, Janet; Emery, Jon; Farmer, Andrew; Griffiths, Frances; Guthrie, Bruce; Lester, Helen; Wilson, Phil; Kinmonth, Ann Louise
Abstract : Determining the effectiveness of complex interventions can be difficult and time consuming. Neil C Campbell and colleagues explain the importance of ground work in getting usable results